THE EFFICACY OF PHARMACOKINETIC MODELING IN DRUG DOSAGE OPTIMIZATION - Hussain Hamad Alhussain, Ahmed Nawaf Naif Alotaibi, Waleed Abdullah Mohammed Alharbi, Ayman Ibrahim Mohammed Almamari, Yasser Ali Alraffaa, Reem Ibrahim Abdullah Alsultan, Jaber Suliman Aljabr, Faiz Ali Almutairi; Naif Eid Alosaimi, Fatimah Abdulmohsen Alhejji, Sulaiman Omar Aljasir, Bandr Turki Alharbi, Faiz Fahd Mubarak, Mohammed Mubarak, Al-othahaimin,abdulrahman Saad Almalki (Chelonian Research Foundation, 2022)
Precision dosage in cancer has significant appeal for several reasons. A significant number of anticancer medications have a limited range of effectiveness, such that inadequate treatment might result in serious consequences for the patient. Recruitment of clinical research participants is seldom expanded outside the target patient group, resulting in challenges in enrolling patients for specific clinical studies. Given the significant number of individuals who do not react to cancer therapy and the expensive nature of such treatments, it is necessary to explore new approaches that might enhance clinical efficacy and cost-benefit. Pharmacokinetic (PK) modeling and model-informed precision dosing (MIPD) provide potential solutions to optimize these outcomes. Pharmacokinetic (PK) modeling offers a precise method to measure and analyze the differences in drug exposure across individuals, taking into consideration factors such as confounders and the effects of drug interactions. This is achieved via the use of physiologically-based PK (PBPK) modeling, which allows for accurate predictions in particular populations and the extrapolation of data. This article provides an overview of the current status of pharmacokinetic (PK) modeling in precision dosing of anticancer medications. The information is derived from a thorough assessment of the literature and includes several case studies from both the pharmaceutical business and healthcare research. Although significant advancements have been achieved in incorporating model-informed dose recommendations into prescription labels and much research has been conducted to address dosing concerns that are important in clinical settings, the use of MIPD in healthcare has been limited. The efficacy of pharmacokinetic (PK) modeling in the industrial sector has been facilitated by cooperative efforts among regulatory bodies, the private sector, and educational institutions. In order to promote the broader use of PK modeling in precision dosing of anticancer medications, it is crucial to establish collaboration between academia, healthcare, and industry. Additionally, financial support for studies on patient benefit, cost-benefit analysis, and clinical success of these techniques is essential. Keywords: Population pharmacokinetics (PK); physiologically-based pharmacokinetics (PBPK); modeling; customized dose; cancer.